Analysis of NLR, HDL, and Hs-Troponin I as A Diagnostic Marker in STEMI and NSTEMI Patients - Yunianingsih Selanno; Darmawaty ER; Sulina Yanti Wibawa; Agus Alim Abdullah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
The limitations of health facilities in diagnosing AMI, especially in remote areas require an easy and inexpensive examination such as Neutrophil Lymphocyte Ratio (NLR) and High-Density Lipoprotein (HDL), which have a positive correlation with hs-Troponin I. The purpose of this study was to analyze the value of NLR, HDL, and hs-Troponin I as diagnostic markers in STEMI and NSTEMI patients. This retrospective study used medical record data for 152 STEMI patients and 93 NSTEMI patients from January to December 2020 at Dr. Wahidin Sudirohusodo. The NLR value was based on the results of routine blood tests using Sysmex XN-10, the results of HDL examinations using the Bio Majesty JCA-BM9010/c instrument, and the results of the hs-Troponin I examination using the Vidas instrument. Statistical tests using the MannWhitney test, the diagnostic value of NLR, and hs-Troponin I was analyzed by ROC to obtain the cut-off. The test result is significant if p <0.05. The sample consisted of 152 samples of STEMI patients and 93 NSTEMI patients. The NLR value in STEMI patients was significantly different from NSTEMI patients (p <0.001), HDL levels were not significantly different in STEMI and NSTEMI patients (p=0.475), while hs-Troponin I levels were significantly higher in STEMI patients than NSTEMI (p <0.001). The ROC curve showed the sensitivity and specificity of NLR, namely 64% and 70% at the cut-off of 4.32, and the sensitivity and specificity of hs-Troponin I was 78% and 60% at the cut-off of 910.5 ng /L. The NLR and hs-Troponin I values was increased in STEMI patients compared to NSTEMI due to the increased inflammatory response and the higher risk of damage to the myocardium. The coordinates of the NLR ROC curve show a cut-off of 4.32 and hs-Troponin I 910.5 ng/L provides optimal sensitivity and specificity. The conclusion of this study is NLR and hs-Troponin I can be used as diagnostic markers in STEMI and NTEMI patients with a cut-off value of NLR 4.32 and hs-Troponin I 910.5 ng/L.